Paying for Permanence: Public Preferences for Contaminated Site Cleanup - Anna Alberini; Stefania Tonin; Margherita Turvani; Aline Chiabai (Fondazione Eni Enrico Mattei (FEEM), 2006)
We use conjoint choice questions to investigate people s preferences for income and reductions in mortality risks delivered by contaminated site remediation policies. Our survey is self-administered using the computer by residents of four cities in Italy with severely contaminated sites. We estimate the Value of a Statistical Life to be about exteuro5.6 million for an immediate risk reduction. If the risk reduction takes place 20 years from now, however, the implied VSL is about exteuro1.26 million. The discount rate implicit in the responses to the conjoint choice questions is about 7%. People are willing to pay for permanent risk reductions, but not just any amount. Risk reductions in the nearer future are valued more highly than risk reductions in the more distant future. We also find that the VSL is individuated, in the sense that it depends on observable individual characteristics of the respondents, familiarity with contaminated sites, concern about the health effects of exposure to toxicants, having a family member with cancer, perceived usefulness of possible government actions, and the respondent s beliefs about the goals of government remediation programs. Additional questions suggest that respondents discount lives, and do so at a discount rate in the ballpark of that implicit in their risk v. money tradeoffs.
Keywords: J17; I18; K32; Q51; Q53; 330; Value of a Statistical Life; Latent Risk Reductions; Individual Discount Rates; Conjoint Choice Questions; Contaminated Sites; Remediation; Umweltsanierung; Gesundheitsrisiko; Willingness to pay; Menschen; Bewertung; Italien; Wert des Lebens